GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 994 species occurrences available in GBIF matching the query: TaxonKey: Hiraea fagifolia (DC.) A. Juss.. The dataset includes 994 records from 74 constituent datasets: 3 records from JOI - Herbário Joinvillea. 16 records from HUEM - Herbário da Universidade Estadual de Maringá. 1 records from HUFU - Herbarium Uberlandense. 6 records from Phanerogamic Botanical Collections (S). 1 records from IAC - Herbário do Instituto Agronômico de Campinas. 1 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 60 records from Naturalis Biodiversity Center (NL) - Botany. 3 records from SPSF - Herbário Dom Bento José Pickel. 38 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 4 records from HERBAM - Herbário da Amazônia Meridional. 4 records from ICN - Herbário do Instituto de Ciências Naturais. 6 records from Herbario Universidad de Antioquia (HUA). 6 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 4 records from CESJ - Herbário Leopoldo Krieger. 5 records from HAMAB - Herbário Amapaense. 33 records from Plantae of Costa Rica (INBio). 37 records from MBM - Herbário do Museu Botânico Municipal. 12 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Digital Florula - Las Cruces Biological Station. 29 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 2 records from Australia's Virtual Herbarium. 4 records from HUCS - Herbário da Universidade de Caxias do Sul. 1 records from ALCB - Herbário Alexandre Leal Costa. 1 records from NMNH occurrence DwC-A. 1 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 2 records from EFC - Herbário Escola de Florestas Curitiba. 3 records from UEC - Herbário da Universidade Estadual de Campinas. 24 records from FUEL - Herbário da Universidade Estadual de Londrina. 6 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 295 records from Tropicos Specimen Data. 5 records from Natural History Museum (London) Collection Specimens. 1 records from Contribución al conocimiento de la flora útil de la selva Lacandona. 2 records from The AAU Herbarium Database. 16 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 14 records from herbario. 2 records from Herbarium (UNA). 9 records from MEXU/Herbario Los Tuxtlas. 6 records from Biologiezentrum Linz. 1 records from Harvard University Herbaria. 1 records from CVRD - Herbário da Reserva Natural Vale. 72 records from Field Museum of Natural History (Botany) Seed Plant Collection. 4 records from MBML-Herbario - Herbário Mello Leitão. 1 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 1 records from MEXU/Flora de Oaxaca. 1 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 10 records from UPCB - Herbário do Departamento de Botânica. 2 records from HVAT - Herbário do Vale do Taquari. 3 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 86 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 6 records from FURB - Herbário Dr. Roberto Miguel Klein. 12 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 3 records from UFACPZ - Herbário da Universidade Federal do Acre. 9 records from Instituto de Ciencias Naturales. 1 records from Type herbarium, Göttingen (GOET). 5 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 16 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 15 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 1 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 20 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 2 records from SLUI - Herbário Rosa Mochel. 3 records from UB - Herbário da Universidade de Brasília. 3 records from Instituto de ciencias naturales. 1 records from Herbarium - Las Cruces Biological Station. 6 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 1 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 2 records from Colección Nacional de Actuopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 7 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 2 records from Herbarium Erlangense. 5 records from SysTax - Herbaria. 5 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 8 records from Geneva Herbarium – General Collection (G). 13 records from Instituto de Botánica Darwinion. 1 records from CPAP - Herbário CPAP. 1 records from PACA-AGP - Herbarium Anchieta.
Keywords: GBIF; biodiversity; species occurrences